Growth arrest and DNA damage-inducible protein 34 (GADD34) contributes to cerebral ischemic injury and can be detected in plasma exosomes. (27th July 2021) - Yang, Tianhui; He, Ruyi; Li, Gongzhe; Liang, Jia; Zhao, Liang; Zhao, Xing; Li, Liyang; Wang, Peng
Graphical abstract: Highlights: GADD34 was increased in the cerebral cortex of rats after ischemic stroke. GADD34 inhibitor attenuated ischemic brain injury. GADD34 inhibitor decreased the levels of eIF2α and p-p53 in ischemic rats. GADD34 was increased in plasma exosomes of cerebral ischemic rats. Abstract: Growth arrest and DNA damage-inducible protein 34 (GADD34), one of the key effectors of negative feedback loops, is induced by stress and subsequently attempts to restore homeostasis. It plays a critical role in response to DNA damage and endoplasmic reticulum stress. GADD34 has opposing effects on different stimulus-induced cell apoptosis events in many nervous system diseases, but its role in ischemic stroke is unclear. In this study, we evaluated the role of GADD34 and its distribution in a rat cerebral ischemic model. The results showed that GADD34 was increased in the cortex and contributed to brain injury in ischemic rats. Furthermore, treatment with a GADD34 inhibitor reduced the infarct volume, improved functional outcomes, and inhibited neuronal apoptosis in the cortical penumbra after ischemia. The role of GADD34 in ischemic stroke was associated with the dephosphorylation of eukaryotic translation initiation factor 2α (eIF2α) and phosphorylation of p53. In addition, the GADD34 level was increased in plasma exosomes of cerebral ischemic rats. These findings indicate that GADD34 could be a potential therapeutic target and biomarker for ischemic stroke.